Pemeriksaan Golongan Darah pada Siswa Kelas VIII MTsS Pondok Pesantren Darul Qur’an Desa Tambak Rejo - Nasution, Irda Wahidah; Hidayah Nasution, Nurul (Edumedia Solution, 2023)
Blood type is very basic and important in human life because it is hereditary (offspring) from parents. The term blood group refers to the entire blood group system that consists of antigens on red blood cells. Blood type refers to the specific reaction pattern of the antiserum given. Since its discovery by Karl Landsteiner in 1901, blood groups have contributed to the understanding of the mechanisms of heredity today. In this world, there are actually about 46 types of antigens besides the A-B-O antigens, it's just that they are much rarer. The method used is a blood group examination free of charge. The dedication activity in the form of checking blood type was carried out at MTsS Darul Qur'an Islamic Boarding School which is located on Jalan Tambak Rejo Medan Amplas, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province. The target audience for this service activity is class VIII students. This service activity was carried out on February 16, 2022, from 09.00-13.00 WIB. The procedure for implementing community service consists of three stages including surveys and interviews, preparation, and implementation. Based on the blood group examination results as presented in Figure 3, it can be seen that the proportion for blood group A is 30.8%, blood group B is 23.0% and blood type O is 38.5% while the proportion for blood group The lowest AB is 7.7%.